Cyprus : Fourth Review under the Extended Arrangement under the Extended Fund Facility and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
This paper focuses on Cyprus' Fourth Review Under the Extended Arrangement Under the Extended Fund Facility (EFF) and Request for Modification of Performance Criteria. The program remains on track. Fiscal targets for the first quarter were met with considerable margins, domestic payment restrictions were fully lifted, and the coop sector was consolidated. The authorities intensified efforts to overcome delays in the implementation of structural measures. There are three key policy challenges: (1) addressing the high level of nonperforming loans; (2) maintaining fiscal sustainability; and (3) strengthening institutions to support fiscal consolidation efforts and long-run growth. Risks to the program remain significant, in particular those related to still strong macro-financial linkages.